Environmental approaches in productivity analysis. Improving proposals - Alexandru Jivan; Miruna-Lucia Nachescu (CES Working Papers, 2019)
Switching the angle of concern from the most usual one, our paper focuses rather on the “external” effects of the economic activities. It aims at reconsidering the useful effects of productive activities by applying specific reinterpretation of usual data, having in mind the general economic-social welfare. Methodologically, the indicators we propose for this purpose use simple ratios, logarithmic summaries and some simple summation, and certain completions, in an original approach. The analysis of the economic activity is proposed in terms of certain effects on the natural environment and on the economic and social environment, upstream and downstream of the studied activity (different than the effects on the economic entity itself), directly targeted. Other connections in the systemic environment are also concerned, suggestions for more applied researches being provided. The paper is a purely theoretical one, presenting just certain researches with their conceptual explanations and also with suggestions for future developments and for empirical applications. It brings interesting openings to the common productivity analysis. The formulas (serviceability ratios) in which the available existing indicators (data) can be included allow us to obtain meanings that are less or are not had in view, in the usual productivity calculations. By applying such proposals, interesting differences between the analysed economic entities can result; and also differences between the common productivity (in “internal” benefit, serviceable for the companies themselves) and the environmental effects (that concern just the “external” serviceability).
Keywords: 330; productivity; serviceability; servicity; production; job creation; heterodox approach